Pharmacokinetic, Pharmacogenetic, and Other Factors Influencing CNS Penetration of Antiretrovirals - Jacinta Nwamaka Nwogu; Qing Ma; Chinedum Peace Babalola; Waheed Adeola Adedeji; Gene D. Morse; Babafemi Taiwo (AIDS Research and Treatment)
Neurological complications associated with the human immunodeficiency virus (HIV) are a matter of great concern. While antiretroviral (ARV) drugs are the cornerstone of HIV treatment and typically produce neurological benefit, some ARV drugs have limited CNS penetration while others have been associated with neurotoxicity. CNS penetration is a function of several factors including sieving role of blood-brain and blood-CSF barriers and activity of innate drug transporters. Other factors are related to pharmacokinetics and pharmacogenetics of the specific ARV agent or mediated by drug interactions, local inflammation, and blood flow. In this review, we provide an overview of the various factors influencing CNS penetration of ARV drugs with an emphasis on those commonly used in sub-Saharan Africa. We also summarize some key associations between ARV drug penetration, CNS efficacy, and neurotoxicity.